Preparation method of polyester-based composite hydrophilic material
By fibrillating, surface amination, amine decomposition and cross-linking treatment of waste polyester fabrics, polyester-based composite hydrophilic materials were prepared, which solved the problems of recycling and utilization of waste polyester fibers and preparation of hydrophilic materials, and achieved efficient material recycling and excellent adsorption properties.
Patent Information
- Application Number
- CN202510049775.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-13
AI Technical Summary
It is difficult for the prior art to effectively recover and utilize waste polyester fibers with high polymerization degree and to prepare hydrophilic materials with excellent adsorption properties.
By fibrillating the waste polyester fabric and surface amination with diethylene triamine, followed by amine decomposition reaction and preparation of crosslinking liquid, the amination polyester fiber is finally crosslinked and composited in the crosslinking liquid to prepare a polyester-based composite hydrophilic material.
It has realized the conversion of waste polyester fibers into composite materials with excellent hydrophilic properties, has high adsorption capacity, and is suitable for water treatment and environmental governance.
Smart Images

Figure CN119793424A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption material preparation, and relates to a method for preparing a hydrophilic adsorption material based on polyester fiber degradation. Background Art
[0002] Polyester fiber is a common polymer material. Due to its excellent physical and chemical properties, it has been widely used in the textile industry, but it also leads to the generation of a large amount of waste polyester fabrics. As the world's largest producer and consumer of textile fibers, China's output of waste polyester fabrics is particularly impressive. According to statistics from the China Chemical Fiber Industry Association, the domestic stock of waste textiles is nearly 400 million tons, of which polyester fibers account for a large proportion.
[0003] The recycling technology of waste polyester fabrics mainly includes physical method, chemical method and physical and chemical method. Although the recycling technology of waste polyester fabrics based on various methods has made certain progress, the overall recycling rate is still low. It is imperative to actively explore the recycling technology of waste polyester fabrics.
[0004] To ensure the "green" and sustainable use of petrochemical resources, more and more researchers are working hard to transform and reuse waste polymers through chemical degradation, such as depolymerizing polyester fabrics into useful low-molecular-weight intermediate materials. However, how to recycle polyester fibers with high polymerization degree and further prepare more functional materials, especially hydrophilic materials, remains a challenge.
[0005] Hydrophilic materials have good water dispersibility and wettability, can form hydrogen bonds with water molecules, and can be used as adsorbent materials to effectively adsorb pollutants in water. Based on the excellent adsorption performance of hydrophilic adsorbent materials, they have been widely used in water treatment, environmental governance and other fields. In water treatment, hydrophilic adsorbents can effectively remove harmful substances such as heavy metal ions and organic pollutants in water and improve water quality; in the field of environmental governance, hydrophilic adsorbents can be used in soil remediation, air purification and other aspects, which has a positive effect on improving environmental quality.
[0006] The use of waste polyester fibers to prepare hydrophilic materials can not only provide a recycling method for waste polyester, but also solve the problem of resource waste to a certain extent, which has huge social and economic benefits. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a polyester-based composite hydrophilic material, so as to utilize waste polyester fabrics to prepare a composite hydrophilic material with excellent hydrophilic properties for use as an adsorption material.
[0008] Based on the above invention objectives, the present invention first provides a method for preparing a polyester-based composite hydrophilic material, which specifically includes:
[0009] S1, shearing small pieces of waste polyester fabric in a pulverizer to partially fibrillate the fibers to obtain fibrillated polyester fibers;
[0010] S2, treating the surface of the fibrillated polyester fiber with a 5-30wt% diethylenetriamine aqueous solution to obtain an aminated polyester fiber;
[0011] S3, in the presence of zinc acetate catalyst, using small pieces of waste polyester fabric and diethylenetriamine to carry out an amination reaction to obtain a polyester amination solution;
[0012] S4, diluting the polyester aminolysis solution with 5 to 10 times the volume of water, and reacting with ethylene glycol glycidyl ether to prepare a crosslinking solution;
[0013] S5. Take the aminated polyester fiber, immerse it in a cross-linking solution for cross-linking and composite treatment, and then dry it to obtain a polyester-based composite hydrophilic material.
[0014] Furthermore, the surface amination treatment process is preferably carried out at 80-140°C.
[0015] Furthermore, the surface amination treatment time is preferably 5 to 15 minutes.
[0016] Furthermore, in the aminolysis reaction, the suitable amount of diethylenetriamine is 3 to 5 times the mass of the waste polyester fabric.
[0017] Furthermore, the aminolysis reaction is preferably carried out under reflux at 160-175° C. to ensure that all the polyester fibers can be completely aminolyzed.
[0018] More preferably, the aminolysis reaction may be first carried out at 110-120° C. for 25-40 min, and then heated to 160-175° C. for 30-45 min.
[0019] Furthermore, the present invention preferably dilutes the polyester aminolysis solution with water, heats it to 100-110° C., adds ethylene glycol glycidyl ether, stirs it for 1-3 minutes, and then cools it to 60-80° C. to perform a crosslinking reaction to prepare a crosslinking solution.
[0020] Wherein, the dosage of the ethylene glycol glycidyl ether is preferably 0.75 to 1.1 times the volume of the polyester aminolysis solution.
[0021] Furthermore, the cross-linking reaction time is preferably 10 to 30 minutes.
[0022] Furthermore, in the present invention, the aminated polyester fiber is immersed in a crosslinking liquid for crosslinking and composite treatment, preferably first placed at 50-80° C. for 2-4 hours and then placed at room temperature overnight.
[0023] Finally, the aminated polyester fiber after the cross-linking composite treatment is taken out, washed with water and then freeze-dried to prepare the polyester-based composite hydrophilic material of the present invention.
[0024] By adopting the preparation method of the present invention, a fluffy polyester-based composite hydrophilic material is finally prepared. The static water contact angle of the fluffy polyester-based composite hydrophilic material is tested to be no more than 30°, and the fluffy polyester-based composite hydrophilic material has excellent hydrophilic properties.
[0025] Therefore, the present invention also provides the use of the polyester-based composite hydrophilic material as an adsorption material, especially as an adsorption material in the field of water treatment.
[0026] More specifically, the polyester-based composite hydrophilic material of the present invention can be used as an adsorption material and applied to the fields of dye wastewater treatment and the like.
[0027] The invention forms a hydrophilic structure with an amine group on the surface of the polyester fiber through the aminolysis of diethylenetriamine on the surface of the polyester fiber, so that the hydrophobic surface of the polyester fiber is changed into a hydrophilic surface; further, the invention obtains a cross-linking liquid by cross-linking the aminolysis liquid obtained by completely aminolyzing the polyester fiber, and further cross-links and solidifies the aminated polyester fiber with the cross-linking liquid, so as to finally obtain a polyester-based composite hydrophilic material with good hydrophilic property.
[0028] The composite hydrophilic material of the present invention is composed of surface aminated polyester fibers and gel formed by curing a crosslinking liquid. The aminated polyester fibers are bonded together by the gel and the material can maintain a certain shape. Both materials contain a large number of amine groups, which makes them excellent in hydrophilicity. At the same time, the composite hydrophilic material has a dense pore structure formed by crosslinking of complete aminolysis products and a macroporous structure formed between the surface aminated polyester fibers, which gives the prepared material a high specific surface area and pore volume, and enhances its adsorption capacity.
[0029] The invention uses waste polyester fabric as raw material, which is of great significance for effectively utilizing waste resources and protecting the environment. The invention has simple preparation process, high efficiency, low energy consumption, low cost, no pollution, and can be recycled. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron microscope image of fibrillated polyester fiber.
[0031] Figure 2 This is the macroscopic morphology and scanning electron microscope image of the composite hydrophilic material prepared in Example 1.
[0032] Figure 3 The static water contact angle comparison between the composite hydrophilic material prepared in Example 1 and the untreated polyester fiber.
[0033] Figure 4 The adsorption performance of the composite hydrophilic material prepared in Example 1 on methylene blue.
[0034] Figure 5 This is the static water contact angle of the composite hydrophilic material prepared in Example 2.
[0035] Figure 6 This is the static water contact angle of the composite hydrophilic material prepared in Example 3.
[0036] Figure 7 This is the static water contact angle of the composite hydrophilic material prepared in Example 4.
[0037] Figure 8 This is the static water contact angle of the composite hydrophilic material prepared in Example 5.
[0038] Fig. 9 This is the static water contact angle of the composite hydrophilic material prepared in Example 6.
[0039] Fig.10 This is the static water contact angle of the composite hydrophilic material prepared in Example 7.
[0040] Fig.11 This is the static water contact angle of the composite hydrophilic material prepared in Example 8.
[0041] Fig.12 This is the static water contact angle of the composite hydrophilic material prepared in Example 9.
[0042] Fig.13 This is the static water contact angle of the composite hydrophilic material prepared in Example 10.
[0043] Fig.14 This is the static water contact angle of the composite hydrophilic material prepared in Example 11.
[0044] Fig.15 This is the static water contact angle of the composite hydrophilic material prepared in Example 12.
[0045] Fig.16 This is the static water contact angle of the composite hydrophilic material prepared in Example 13. Implementation
[0046] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.
[0047] The production processes, experimental methods or detection methods involved in the embodiments and comparative examples of the present invention are all conventional methods in the prior art unless otherwise specified, and their names and / or abbreviations are all conventional names in the field and are very clear and unambiguous in the relevant application fields. Technicians in the field can understand the conventional process steps based on the names and apply the corresponding equipment to implement them according to conventional conditions or the conditions recommended by the manufacturer.
[0048] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art. Example
[0049] Example 1
[0050] The waste polyester fabric is cut into small pieces, put into a pulverizer, and further sheared to fibrillate the fiber part to obtain fibrillated polyester fiber.
[0051] Figure 1 The scanning electron microscope image of fibrillated polyester fiber is given. When the fabric is sheared, loosened and dispersed, the fiber is split along the axial direction under the action of shear and mechanical friction, and fine microfibrils are split on the fiber surface, achieving partial fibrillation of the fiber, which is beneficial to increase the degree of subsequent amination reaction.
[0052] 0.2 g of the fibrillated polyester fiber was weighed and placed in 20 ml of a 20% diethylenetriamine aqueous solution, and immersed in the solution for reaction at 130° C. for 10 min to obtain an aminated polyester fiber with the surface subjected to an amination treatment.
[0053] Weigh 1 g of small pieces of waste polyester fabric into a round-bottom flask with a stirrer and a reflux condenser, add 4 g of diethylenetriamine and 0.01 g of zinc acetate, first react at 120 ° C for 30 min, then heat to 170 ° C for 20 min to ensure that the fiber is completely aminolyzed to obtain a polyester aminolyzate.
[0054] Take 2 ml of polyester aminolysis solution, add it into 10 ml of deionized water, heat it to 110° C., add 2 ml of ethylene glycol glycidyl ether, stir for 1 min, cool it to 60° C., stir and react for 10 min, and prepare a cross-linking solution.
[0055] Weigh 0.2 g of aminated polyester fiber, completely immerse it in the above cross-linking solution, stand it at 60° C. for 2 h, then leave it at room temperature overnight, take it out, wash it with deionized water, and freeze-dry it to prepare a polyester-based composite hydrophilic material.
[0056] Figure 2These are the macroscopic morphology and scanning electron microscope images of the prepared polyester-based composite hydrophilic material. It can be seen that the composite hydrophilic material has a fluffy appearance and a rich pore structure. Further, from the SEM image, it can be observed that the composite hydrophilic material is full of a dense pore structure formed by cross-linking of complete amination products and a macroporous structure formed between aminated polyester fibers, thereby giving the composite hydrophilic material a high specific surface area and pore volume and enhancing its adsorption capacity.
[0057] Since the composite hydrophilic material structure contains a large number of amine groups, the material is endowed with good water wettability. According to the test, its static water contact angle is only 4°, while the static water contact angle of the untreated polyester fiber is 110°. Therefore, the present invention changes the polyester fiber from hydrophobic to hydrophilic. The specific test results are as follows: Figure 3 .
[0058] The composite hydrophilic material prepared by the present invention also has good adsorption capacity, such as Figure 4 As shown, after testing, it has good adsorption performance for 1g / L methylene blue solution, and the adsorption amount can reach 500mg / g, and can be used as an adsorption material.
[0059] Example 2
[0060] The concentration of the diethylenetriamine aqueous solution in the surface amination treatment step was adjusted to 5%, and the treatment conditions were immersion reaction at 80° C. for 15 min. Other conditions were the same as those in Example 1, and a polyester-based composite hydrophilic material was prepared.
[0061] like Figure 5 , the static water contact angle of the tested composite hydrophilic material is 30°.
[0062] Example 3
[0063] The concentration of the diethylenetriamine aqueous solution in the surface amination treatment step was adjusted to 10%, and the treatment conditions were immersion reaction at 100° C. for 15 min. Other conditions were the same as those in Example 1, and a polyester-based composite hydrophilic material was prepared.
[0064] like Figure 6 , the static water contact angle of the tested composite hydrophilic material is 10°.
[0065] Example 4
[0066] The concentration of the diethylenetriamine aqueous solution in the surface amination treatment step was adjusted to 10%, and the treatment conditions were immersion reaction at 140° C. for 5 min. Other conditions were the same as those in Example 1, and a polyester-based composite hydrophilic material was prepared.
[0067] like Figure 7 , the static water contact angle of the tested composite hydrophilic material is 20°.
[0068] Example 5
[0069] The concentration of the diethylenetriamine aqueous solution in the surface amination treatment step was adjusted to 20%, and the treatment conditions were immersion reaction at 140° C. for 10 min. Other conditions were the same as those in Example 1, and a polyester-based composite hydrophilic material was prepared.
[0070] like Figure 8 , the static water contact angle of the tested composite hydrophilic material is 10°.
[0071] Example 6
[0072] The concentration of the diethylenetriamine aqueous solution in the surface amination treatment step was adjusted to 30%, and the treatment conditions were immersion reaction at 100° C. for 10 min. Other conditions were the same as those in Example 1, and a polyester-based composite hydrophilic material was prepared.
[0073] like Fig. 9 , the static water contact angle of the tested composite hydrophilic material is 20°.
[0074] Example 7
[0075] The concentration of the diethylenetriamine aqueous solution in the surface amination treatment step was adjusted to 30%, and the treatment conditions were immersion reaction at 140° C. for 5 min. Other conditions were the same as those in Example 1, and a polyester-based composite hydrophilic material was prepared.
[0076] like Fig.10 , the static water contact angle of the tested composite hydrophilic material is 5°.
[0077] Example 8
[0078] In the step of adjusting the cross-linking solution preparation, 2 ml of polyester aminolysis solution was added into 15 ml of deionized water. Other conditions were the same as those in Example 1, and a polyester-based composite hydrophilic material was prepared.
[0079] like Fig.11 , the static water contact angle of the tested composite hydrophilic material is 10°.
[0080] Example 9
[0081] In the step of adjusting the preparation of the cross-linking solution, 2 ml of the polyester aminolysis solution was added into 20 ml of deionized water. Other conditions were the same as those in Example 1, and a polyester-based composite hydrophilic material was prepared.
[0082] like Fig.12 , the static water contact angle of the tested composite hydrophilic material is 0°.
[0083] Example 10
[0084] The aminolysis reaction was adjusted to react at 110°C for 40 minutes, and then heated to 175°C for 40 minutes; 1.1 times the volume of the polyester aminolysis solution was added to prepare a crosslinking solution; the aminated polyester fiber was immersed in the crosslinking solution, first placed at 80°C for 4 hours for crosslinking and compounding, and then placed at room temperature overnight. The other conditions were the same as in Example 1, and a polyester-based composite hydrophilic material was prepared.
[0085] like Fig.13 , the static water contact angle of the tested composite hydrophilic material is 0°.
[0086] Embodiment 11
[0087] The concentration of the diethylenetriamine aqueous solution in the surface amination treatment step was adjusted to 10%, and the reaction was carried out at 100°C for 5 minutes; the aminolysis reaction was first carried out at 110°C for 25 minutes, and then the temperature was raised to 160°C for 25 minutes; 0.75 times the volume of the polyester aminolysis solution was added to prepare a crosslinking solution; the aminated polyester fiber was immersed in the crosslinking solution, first placed at 50°C for 2 hours for crosslinking and compounding, and then placed at room temperature overnight. The other conditions were the same as those in Example 1, and a polyester-based composite hydrophilic material was prepared.
[0088] like Fig.14 , the static water contact angle of the tested composite hydrophilic material is 20°.
[0089] Example 12
[0090] The aminolysis reaction was adjusted to react at 115°C for 35 minutes, and then heated to 170°C for 35 minutes; 1.1 times the volume of the polyester aminolysis solution was added with ethylene glycol glycidyl ether, stirred for 2 minutes, and cooled to 80°C for cross-linking reaction for 30 minutes to prepare a cross-linking solution; the aminated polyester fiber was immersed in the cross-linking solution, first placed at 80°C for 4 hours for cross-linking and compounding, and then placed at room temperature overnight. The other conditions were the same as in Example 1, and a polyester-based composite hydrophilic material was prepared.
[0091] like Fig.15 The static water contact angle of the tested composite hydrophilic material is 15°.
[0092] Example 13
[0093] The aminolysis reaction was adjusted to react at 110°C for 40 minutes, and then heated to 165°C for 45 minutes; ethylene glycol glycidyl ether was added to the polyester aminolysis solution dilution solution and stirred for 2 minutes, and then cooled to 80°C for cross-linking reaction for 20 minutes to prepare a cross-linking solution; the aminated polyester fiber was immersed in the cross-linking solution, first placed at 70°C for 3 hours for cross-linking and compounding, and then placed at room temperature overnight. The other conditions were the same as in Example 1, and a polyester-based composite hydrophilic material was prepared.
[0094] like Fig.16, the static water contact angle of the tested composite hydrophilic material is 0°.
[0095] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a polyester-based composite hydrophilic material, comprising: S1, shearing small pieces of waste polyester fabric in a pulverizer to partially fibrillate the fibers to obtain fibrillated polyester fibers; S2, treating the surface of the fibrillated polyester fiber with a 5-30wt% diethylenetriamine aqueous solution to obtain an aminated polyester fiber; S3, in the presence of zinc acetate catalyst, using small pieces of waste polyester fabric and diethylenetriamine to carry out an amination reaction to obtain a polyester amination solution; S4, diluting the polyester aminolysis solution with 5 to 10 times the volume of water, and reacting with ethylene glycol glycidyl ether to prepare a crosslinking solution; S5. Take the aminated polyester fiber, immerse it in a cross-linking solution for cross-linking and composite treatment, and then dry it to obtain a polyester-based composite hydrophilic material.
2. The method for preparing a polyester-based composite hydrophilic material according to claim 1, characterized in that The surface amination treatment is carried out at 80-140° C. for 5-15 minutes.
3. The method for preparing a polyester-based composite hydrophilic material according to claim 1, characterized in that The aminolysis reaction is carried out under reflux at 160-175° C., and the amount of diethylenetriamine used is 3-5 times the mass of the waste polyester fabric.
4. The preparation method according to claim 3, characterized in that The aminolysis reaction is first reacted at 110-120°C for 25-40 minutes, and then heated to 160-175°C for 30-45 minutes.
5. The method for preparing a polyester-based composite hydrophilic material according to claim 1, characterized in that the polyester aminolysis solution is diluted with water, heated to 100-110°C, 0.75-1.1 times the volume of the polyester aminolysis solution of ethylene glycol glycidyl ether is added, stirred for 1-3 minutes, and then cooled to 60-80°C for cross-linking reaction to prepare a cross-linking solution.
6. The preparation method according to claim 5, characterized in that The cross-linking reaction time is 10 to 30 minutes.
7. The method for preparing a polyester-based composite hydrophilic material according to claim 1, characterized in that The aminated polyester fiber is immersed in a crosslinking solution, first placed at 50-80° C. for 2-4 hours, and then placed at room temperature overnight for crosslinking and composite treatment.
8. The polyester-based composite hydrophilic material prepared by the preparation method according to claim 1, wherein the static water contact angle of the polyester-based composite hydrophilic material is not greater than 30°.
9. Use of the polyester-based composite hydrophilic material according to claim 8 as an adsorption material.
10. Use of the polyester-based composite hydrophilic material according to claim 8 as an adsorption material for dye wastewater treatment.
Citation Information
Patent Citations
PP-ST-DVB-based cation exchange fiber and synthesis method thereof
CN108187765A
Method for preparing hydrophilic functional fabric from polyester fiber aminated derivative
CN115305720A
Bleaching and dyeing process for cotton fabric
CN115354509A
Preparation method and application of alkylated chitosan / sodium alginate composite sponge material
CN116144068A
Compositions and methods for crossing the blood brain barrier
TW202435912A